SUSTAINABLE DEVELOPMENT IN ARCHITECTURAL EDUCATION - Poslusna, Iva; Urbaskova, Hana (European Scientific Journal, ESJ, 2014)
The Faculty of Architecture of the Brno University of Technology represents an art school at a technical university. That is why its study programmes include subject both from the field of fine arts as well as from technology which get students closer to implement their science. Future architects and urban designers get acquainted with technical creation tools to achieve the goals of their study programmes - to acquire such knowledge and skills to make a BA graduate capable of dealing with designing residential, public and production structures, reconstructions of buildings or their interiors - all that from wider urban relations and basic architectural concept of the work to the urban-design, architectural or technical details. Graduates with Ing. Arch. degree will ten become experts - creative workers who can manage project designing and management activities included in the process of investment development in the whole complex of their profession. We pay close attention to ensure that the education acquired forms basic dispositions for activities which will fulfil all attributes of optimum formation of the environment and principles of sustainable development. The process of architectural creation fulfilment as a scientific path is conclusively demonstrated to students directly in classes, accompanying workshops, involvement in projects with partner schools, towns, professional institutions. The school then presents outputs of their projects, competitions and stays at internships at exhibitions even in renowned galleries, at conferences and in professional press.